Problemes de la història social de la llengua dels segles XIX i XX - Ginebra, Jordi (Caplletra. Revista Internacional de Filologia, 1999)
Reflections on the conditions, contents and methodology of the social history of Catalan, reflections which deal with the 19th and 20th centuries, but go beyond these periods. From a perspective close to that of the sociology of knowledge, the author points out the limitations that threaten the status of this discipline. He points out some problems both in method and exegesis, such as access to data, reliability of these data, interdisciplinary collaboration, the conceptual scope of linguistic change, the distinction between facts and interpretations, and periodization.